The role of mediation in the activities of law enforcement bodies - V. A. Doroshenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the study of such an alternative method of dispute resolution as mediation. Mediation is currently a very popular way of resolving conflicts and is beginning to be introduced into all spheres of human life. Mediation is conducted by mutual consent of the mediation parties, taking into account the principles of voluntariness, confidentiality, neutrality, independence and impartiality of the mediator, self-determination and equality of rights of the mediation parties. The principles of mediation extend to the stage of preparation for mediation.